Mitochondria- and nucleolus-targeted copper(i) complexes with pyrazole-linked triphenylphosphine moieties for live cell imaging. Issue 1 (11th November 2019) - Mayank,; Rani, Richa; Singh, Ashutosh; Garg, Neha; Kaur, Navneet; Singh, Narinder
Abstract : We developed C1 and C2 metallo-complexes as highly efficient cell imaging tools. These complexes enabled us to visualize mitochondria and nucleolus in a single experiment via live cell imaging techniques. Abstract : The labelling and imaging of mitochondria and nucleolus have attracted great attention because of the involvement of these cellular organelles in critical cellular activities. Therefore, a large number of mitochondria- or nucleolus-labelling probes have been developed throughout the world. However, in the current study, we successfully developed two pyrazole-based, copper-linked triphenylphosphine-coupled emissive metallo-complexes (C1 and C2 ) for the simultaneous visualization of mitochondria and nucleolus in a single run. These complexes were very inexpensive and could be synthesized by a simple one-pot multicomponent reaction scheme. The complexes were very specific, and only a small concentration of 5 μM was found to be sufficient to probe both the organelles efficiently. Additionally, even under a shorter incubation period (half hour), the fluorescence intensity from the cells was appreciable. Also, both the compounds were found to be photostable when torched with 10% of a 100 mW laser for up to 10 min. All these results indicate that both the complexes may contribute towards the future development of cell imaging tools. To the best of our knowledge, this is the first report on the development of multifunctional live cell imaging tools for simultaneous mitochondria and nucleolus imaging and within the shortest incubation time of about 30 minutes.